2003
DOI: 10.1128/ec.2.6.1274-1287.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sla1, aSchizosaccharomyces pombeHomolog of the Human La Protein, Induces Ectopic Meiosis when Its C Terminus Is Truncated

Abstract: Sla1 is a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…In an alternative regulatory pathway, Pat1 can be inhibited by a truncated version of Sla1, an ortholog of the mammalian La protein. 13,14) Overexpression of the cyr1 gene results in sterility because the cAMP level is kept high even under nutrient starved conditions. 5) On the contrary, a cyr1 mutant undergoes sexual development even under nutrient rich conditions.…”
mentioning
confidence: 99%
“…In an alternative regulatory pathway, Pat1 can be inhibited by a truncated version of Sla1, an ortholog of the mammalian La protein. 13,14) Overexpression of the cyr1 gene results in sterility because the cAMP level is kept high even under nutrient starved conditions. 5) On the contrary, a cyr1 mutant undergoes sexual development even under nutrient rich conditions.…”
mentioning
confidence: 99%
“…Fragments .4 kb were cloned into the low-copy vector pYC11-ars 3002 1 3 (Dubey et al 1994;Tanabe et al 2003) that had been digested with HindIII or SacI. The S. pombe strain SPRN1DA, which lacks ras1 and cannot sporulate, was transformed by this genomic library, grown for 5 days at 30°, and incubated for 2 days at 25°.…”
Section: Isolation Of a Fission Yeast Homolog Of Zds1 And Zds2mentioning
confidence: 99%
“…Pat1 is inhibited by Mei3, whose expression is induced by the pheromone signaling pathway (Li and McLeod 1996). In an alternative regulatory pathway, Pat1 can be inhibited by a truncated version of Sla1, an ortholog of the mammalian La protein (Tanabe et al 2003(Tanabe et al , 2004.…”
mentioning
confidence: 99%
“…11,12) In addition to these functions, we reported that Sla1 has a novel role in meiosis. 13) Sla1ÁC, a truncated form in the C terminus, which was initially obtained from the screening to rescue the ras1 À phenotype, 13,14) induces ectopic haploid meiosis. This type of haploid meiosis is unique in pat1 ts mutants or a strain that expresses mei2-SATA, a conditional activated mutant of mei2.…”
Section: )mentioning
confidence: 99%